OPTIMAL BY THE CRITERION OF MINIMUM ACCELERATION ENERGY, SYSTEM OF CENTRIFUGAL PUMP HEAD REGULATION - Ostroverkhov Мykola; Buryk Мykola (Scientific Works of Vinnytsia National Technical University, 2018)
Method of hydraulic grid head control process optimization is suggested on the base of the concept of inverse problems of dynamics combined with the minimization of local functionals of instantaneous values of energy that enables to obtain the needed dynamic accuracy of the preset path adjustment in conditions of parametric and coordinate disturbances impact.